THE INFLUENCE OF AUDIO VISUAL AIDS AND LEARNING MOTIVATION TOWARDS TENTH GRADE STUDENTS’ SPEAKING ABILITY AT MAN 1 MUSI BANYUASIN SEKAYU - Kristin Faridawati (Universitas PGRI Palembang, 2022)
The objectives of this research were to find out the influence of audio visual aids toward tenth grade students’ speaking ability, the influence of traditional teaching toward tenth grade students’ speaking ability, the influence of audio visual aid and learning motivation toward tenth grade students’ speaking ability and the interaction effect of audio visual aid and learning motivation toward the students’ speaking ability. In this research, the researcher used Quantitative researh and was conducted utilizing a Factorial design. The population of this researchwas tenth grade students of MAN 1 Musi Banyuasin Sekayu through two stages random sampling. Techniques of collecting data used questionnaireand test. For technique of data analysis used SPSS 16. The result in this research indicated that Audio Visual aids through traditional teaching was developing as an alternative media to help X grade students to learn speaking ability. In other words, the total of all RQ, The null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.